Phytic acid-magnesium synergistically regulated carbon-limited defect vanadyl pentoxide nanoszyme for uric acid colorimetric detection and preparation method thereof
Patent Information
- Application Number
- CN202611485462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的是提供一种用于尿酸比色检测的植酸-镁协同调控碳限域缺陷型V2O5纳米酶及其制备方法,以解决普通V2O5纳米材料在类过氧化物酶催化中存在的孔道结构开放程度较低、比表面积有限、电子传递能力不足、缺陷活性位点较少以及尿酸比色检测灵敏度有限的问题
(1)本发明通过壳聚糖辅助凝胶、冷冻干燥及不同气氛下两段式热处理相结合的方式,构筑了具有疏松片层结构和开放多孔结构的V2O5基纳米酶。所得材料有助于缓解普通V2O5孔结构开放程度有限、活性位点暴露不足的问题。制备的用于尿酸比色检测的植酸-镁协同调控碳限域缺陷型V2O5纳米酶的BET比表面积达到142.6m2/g,孔体积达到0.48cm3/g,明显高于普通V2O5样品。较大的比表面积和孔体积有利于H2O2、TMB等反应底物在材料表面的扩散、吸附和接触,为提高类过氧化物酶催化活性提供了有利的结构基础。
Smart Images

Figure CN122974343A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of nanomaterials, nanostructures and their special applications, and specifically relates to a phytic acid-magnesium synergistic carbon confinement defect type V2O5 nanozyme for colorimetric detection of uric acid and its preparation method. Background Technology
[0002] Uric acid is the end product of purine metabolism in the human body, and abnormal uric acid levels are closely related to hyperuricemia, gout, chronic kidney disease, metabolic syndrome, and cardiovascular diseases. Therefore, establishing rapid, sensitive, and low-cost uric acid detection methods is of great significance for disease screening, treatment monitoring, and health management. Existing uric acid detection methods mainly include enzymatic methods, electrochemical methods, chromatographic methods, and colorimetric methods. Among these, colorimetric detection, due to its simplicity, low cost, and intuitive results, is suitable for primary care and point-of-care testing scenarios and has promising application prospects.
[0003] Currently, commonly used uric acid colorimetric detection systems typically rely on uricase catalyzing the formation of H₂O₂ from uric acid. Then, natural peroxidase (POD) or nanomaterials with peroxidase-like activity catalyze the oxidation of the chromogenic substrate by H₂O₂, achieving indirect uric acid detection. However, natural enzymes suffer from high cost, insufficient stability, strict storage requirements, and susceptibility to inactivation in complex samples, limiting the stability and practical application of the detection system. In contrast, nanozymes offer advantages such as simple preparation, good stability, and easy structural control, attracting widespread attention in H₂O₂ detection and oxidase cascade colorimetric detection.
[0004] V₂O₅ possesses multivalent vanadium centers and certain redox activities, showing potential applications in catalysis and sensing. However, ordinary V₂O₅ typically suffers from low pore structure openness, limited specific surface area, insufficient electron transport capacity, and a limited number of defective active sites, resulting in unsatisfactory peroxidase-like activity. Previous studies have shown that defect construction, morphology regulation, and porous structure design can improve the electronic structure and interfacial reactivity of V₂O₅ materials. However, current V₂O₅-based nanozyme designs still struggle to simultaneously consider factors such as open pore structures, low-valent V sites and oxygen vacancy-related defects, interfacial electron transport, and substrate diffusion contact. Further optimization is needed for specialized structural designs targeting the H₂O₂ activation and TMB colorimetric processes in uric acid colorimetric detection. Summary of the Invention
[0005] The purpose of this invention is to provide a phytic acid-magnesium synergistic carbon-confined defective V2O5 nanozyme for uric acid colorimetric detection and its preparation method, in order to solve the problems of low pore structure openness, limited specific surface area, insufficient electron transfer capacity, few defective active sites, and limited sensitivity of uric acid colorimetric detection in ordinary V2O5 nanomaterials in peroxidase-like catalysis.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A phytate-magnesium synergistically regulated carbon-confined defect V₂O₅ nanozyme for colorimetric detection of uric acid, the nanozyme comprising a V₂O₅ crystalline phase, a carbon-confined structure, and phytate-derived P and Mg components; the nanozyme has an open, porous, loosely layered structure and possesses the following physicochemical characteristics: (a) Surface V 4+ The proportion is no less than 43.9%; (b) The intensity of oxygen vacancy-related electron paramagnetic resonance (EPR) signal was higher than that of control samples regulated by phytate alone or magnesium alone; (c) The charge transfer impedance Rct is not higher than 3.0Ω; (d) The specific surface area of BET is not less than 130m² 2 / g, pore volume not less than 0.40cm³ 3 / g.
[0007] Furthermore, the carbon confined structure exhibits a weak diffraction signal of the carbon (002) crystal plane in the X-ray diffraction pattern within the range of 2θ≈24°~26°.
[0008] This invention also provides a method for preparing a phytic acid-magnesium synergistically regulated carbon-confined defective V2O5 nanozyme for colorimetric detection of uric acid, comprising the following steps: (1) Dissolve ammonium metavanadate in deionized water, stir at 70~85℃ to dissolve, cool and add phytic acid solution, stir at room temperature to obtain vanadium-phytic acid mixed solution; add magnesium chloride hexahydrate to deionized water, sonicate to dissolve, add dropwise to the vanadium-phytic acid mixed solution under stirring, and adjust the pH to 3.5~4.5 with hydrochloric acid to obtain precursor solution; (2) Dissolve chitosan in deionized water containing glacial acetic acid and stir at room temperature to form a chitosan solution. Add the chitosan solution dropwise to the precursor solution in step (1). After the addition is complete, continue stirring to form a composite hydrogel. After washing and freeze-drying, a composite aerogel precursor is obtained. (3) The composite aerogel precursor is placed in a tube furnace and calcined at 470~520℃ under a nitrogen atmosphere for 1.5~2.5h. After natural cooling, it is calcined at 250~300℃ under an air atmosphere for 15~25min to obtain the phytic acid-magnesium synergistic carbon confinement defect type V2O5 nanozyme for uric acid colorimetric detection.
[0009] Further, in step (1), the ratio of ammonium metavanadate to phytic acid is 5.0 mmol of ammonium metavanadate to 85~120 μL of phytic acid solution, and the mass percentage concentration of the phytic acid solution is 70%; the amount of magnesium chloride hexahydrate is 0.4~0.65 mmol.
[0010] Furthermore, in step (1), the molar ratio of P contained in phytic acid to Mg contained in magnesium chloride hexahydrate (P / Mg molar ratio) is 1.1:1 to 2.8:1, more preferably 1.68:1 to 1.94:1.
[0011] Further, in step (2), the amount of chitosan used is 0.15~0.30g, the degree of deacetylation of the chitosan is ≥90%; the amount of glacial acetic acid used is 0.17~0.22mL, the amount of deionized water used is 15~25mL; the freeze-drying temperature is -50 to -40℃, and the time is 22~26h.
[0012] Further, in step (3), the heating rate of the first calcination stage is 5℃ / min, the holding temperature is 490~510℃, and the holding time is 1.8~2.2h; the heating rate of the second calcination stage is 5℃ / min, the holding temperature is 270~290℃, and the holding time is 18~22min.
[0013] Further, the ultrasonic dissolution time in step (1) is 20~40 min, and the pH is adjusted to 4.0; the stirring time after the addition in step (2) is 1~4 h.
[0014] Further, in step (1), the ratio of ammonium metavanadate to deionized water is 5.0 mmol: 70~100 mL; the ratio of magnesium chloride hexahydrate to deionized water is 0.4~0.65 mmol: 15-30 mL; the first stirring time is 25~40 min; the second stirring time is 20~30 min; the concentration of hydrochloric acid is 0.1 mol / L; and the pH is adjusted to 4.0.
[0015] Furthermore, in step (2), the stirring time at room temperature is 1.5~4h; the washing is performed 3 times with deionized water.
[0016] The present invention also provides an application of the above-mentioned phytic acid-magnesium synergistic carbon confinement defective V2O5 nanozyme for uric acid colorimetric detection in the preparation of uric acid detection reagents or detection systems.
[0017] Furthermore, the uric acid detection is a colorimetric detection method. The detection principle is as follows: uric acid is converted to hydrogen peroxide by uricase. This hydrogen peroxide is then catalyzed by the phytic acid-magnesium synergistically regulated carbon-confined defective V2O5 nanozyme used for uric acid colorimetric detection, oxidizing 3,3',5,5'-tetramethylbenzidine (TMB) to produce a blue oxidation product. Quantitative detection of uric acid is achieved by measuring the absorbance change at a wavelength of 652 nm. The linear range of the detection is 5–300 μM, the detection limit is no higher than 4.5 μM, and the recovery rate in artificial serum samples is 98.8%–103.1%, with an intra-assay relative standard deviation (RSD) of less than 5%.
[0018] The beneficial effects of this invention are as follows: (1) This invention constructs a V2O5-based nanozyme with a loose lamellar structure and an open porous structure by combining chitosan-assisted gelation, freeze-drying, and two-stage heat treatment under different atmospheres. The resulting material helps to alleviate the problems of limited pore openness and insufficient exposure of active sites in ordinary V2O5. The prepared phytic acid-magnesium synergistic carbon-confined defective V2O5 nanozyme for uric acid colorimetric detection has a BET specific surface area of 142.6 m². 2 / g, pore volume reaches 0.48cm³ 3 The specific surface area and pore volume are significantly higher than those of ordinary V2O5 samples. The larger specific surface area and pore volume are conducive to the diffusion, adsorption and contact of reaction substrates such as H2O2 and TMB on the material surface, providing a favorable structural basis for improving the catalytic activity of peroxidase-like enzymes.
[0019] (2) In this invention, the phytic acid-derived P and Mg components (P / Mg) have a synergistic regulatory effect on the surface valence state, oxygen vacancy-related defects, pore structure, and interfacial charge transfer ability of V2O5-based nanozymes. In this invention, the molar ratio of P contained in phytic acid to Mg contained in magnesium chloride hexahydrate is controlled within the range of 1.1:1 to 2.8:1. During the precursor formation process, phytic acid molecules contain multiple phosphate groups, which can react with vanadium species and Mg in the system. 2+Coordination, electrostatic interactions, or other interactions occur, affecting the distribution of each component in the precursor and the local chemical environment of the vanadium-oxygen structure. After subsequent carbonization and oxidation treatments, phytic acid-derived phosphorus-containing components are beneficial for regulating the valence state composition of vanadium on the material surface and oxygen vacancy-related defects, while magnesium-containing components are beneficial for regulating the pore structure properties of the material after heat treatment. Thus, the phosphorus (P) component mainly provides defect induction and surface valence state regulation, while the magnesium (Mg) component mainly provides structure-assisted regulation. The two components work together in the same preparation system, enabling the synergistic achievement of defect regulation, pore structure optimization, and charge transfer improvement, which are difficult to achieve simultaneously with a single P or Mg component. When the P / Mg molar ratio is less than 1.1:1, the relative excess of Mg in the system may cause some phosphate groups to preferentially interact with the Mg component, weakening the regulatory effect of P on the VO coordination environment and leading to a decrease in defect induction efficiency. Simultaneously, excess Mg may also reduce the openness of the pores. When the P / Mg molar ratio is higher than 2.8:1, the P component is relatively excessive in the system. Phytic acid molecules and their derivatives may over-cover the V2O5 surface, reducing the effective exposure of active sites and affecting the diffusion and contact of reaction substrates such as H2O2 and TMB to the active interface. Therefore, controlling the P / Mg molar ratio within the range of 1.1:1 to 2.8:1 is beneficial to maximizing the synergistic effect of P-dominated defect induction and Mg-assisted pore structure optimization, thereby obtaining V2O5-based nanozymes with superior peroxidase-like activity. When the P / Mg molar ratio is in the range of 1.68 to 1.94:1, the phosphate groups in the phytic acid molecules react with Mg... 2+ The number of coordination sites reaches a dynamic equilibrium, neither excessively occupying VO sites nor being sufficient to cause Mg to... 2+ Induced aggregation, thereby obtaining the optimal defect-pore structure coupling effect.
[0020] (3) The retention of an appropriate amount of carbon confinement structure in this invention can improve the interfacial electron transfer capability of V2O5-based nanozymes and help maintain the open pore structure. Among them, the sample of Example 1 showed a lower charge transfer impedance, Rct of 2.43Ω, which was significantly lower than that of ordinary V2O5 and the comparative sample, indicating that its interfacial charge transfer resistance was significantly reduced. Compared with the comparative sample with weakened carbon confinement structure, the sample of this invention has lower charge transfer impedance, higher specific surface area and pore volume, and stronger peroxidase-like catalytic response, indicating that the appropriate amount of carbon component is not an ineffective impurity, but works together with the V2O5 host and the P / Mg synergistic regulatory system to play a positive role in promoting electron transfer and stabilizing the porous structure.
[0021] (4) The carbon-confined defective V2O5 nanozyme synergistically regulated by phytic acid-derived P and Mg components obtained in this invention exhibits excellent peroxidase-like catalytic performance and can be used for uric acid oxidase cascade colorimetric detection. After uric acid is catalyzed by uric acid oxidase to generate H2O2, the nanozyme of this invention catalyzes the oxidation of TMB by H2O2 to produce a blue oxidation product, thus converting the change in uric acid concentration into a change in absorbance at 652 nm. A good linear relationship is observed within the uric acid concentration range of 5–300 μM, with a detection limit of 4.5 μM. In artificial serum samples, the uric acid spiked recovery rate is 98.8%–103.1%, and the intra-assay relative standard deviation (RSD) is less than 5%, indicating that the system has good detection sensitivity, accuracy, and repeatability, and possesses the potential for rapid colorimetric detection of uric acid in vitro. Attached Figure Description
[0022] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the sample in Example 1 of this invention. Figure 2 This is a scanning electron microscope image and elemental mapping (SEM EDS-mapping) of the sample in Example 1 of the present invention; Figure 3 The image shows the V 2p high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of the sample in Example 1 of this invention. Figure 4 The electron paramagnetic resonance (EPR) spectra of the samples from Example 1 and Comparative Examples 1-5 of this invention are shown below. Figure 5 The image shows the electrochemical impedance spectroscopy (EIS) diagram of the sample from Example 1 of this invention. Figure 6 The images show the UV-Vis absorption spectra of the TMB-H2O2 systems in Examples 1-3 and Comparative Examples 1-5 of this invention. Figure 7 This is a colorimetric detection diagram of the sample used for uric acid detection in Example 1 of the present invention. Figure 7 In the diagram, 'a' represents the ultraviolet-visible absorption spectrum. Figure 7 (where b represents the standard curve). Figure 8 This is an image showing the anti-interference results of the sample used for uric acid detection in Example 1 of the present invention. Detailed Implementation
[0023] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments. Any conventional adjustments made to the type and amount of raw materials, reaction conditions, heat treatment atmosphere, detection substrate or detection sample under the concept of the present invention shall fall within the scope of protection of the present invention.
[0024] Example 1: (1) Weigh 5.0 mmol NH4VO3 (ammonium metavanadate) and add it to 80 mL of deionized water. Stir and dissolve at 80 °C for 30 min (first stirring). After cooling, a vanadate solution is obtained. Add 100 μL of phytic acid (70%) solution to the above vanadate solution and continue stirring at room temperature for 30 min (second stirring) to obtain a vanadium-phytic acid mixed solution. Add 0.5 mmol MgCl2·6H2O to 20 mL of deionized water and sonicate to dissolve for 30 min. Then, slowly add it dropwise to the above vanadium-phytic acid mixed solution while stirring. Adjust the pH of the mixed system to 4.0 with 0.1 mol / L HCl to finally obtain the precursor solution.
[0025] (2) Take 0.20 g of chitosan with a degree of deacetylation ≥ 90% and add it to 20 mL of deionized water, along with 0.20 mL of glacial acetic acid. Stir at room temperature for 2 h to form a homogeneous chitosan solution. Slowly add the above chitosan solution dropwise to the precursor solution, stirring continuously during the addition process. After the addition is complete, continue stirring for 2 h to form a homogeneous composite hydrogel. Wash the obtained composite gel three times with deionized water. Then place the washed hydrogel in a vacuum freeze dryer and dry at -45℃ for 24 h to obtain the composite aerogel precursor.
[0026] (3) The obtained composite aerogel precursor was placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, and held at that temperature for 2 hours. After natural cooling, it was heated to 280°C at a heating rate of 5°C / min under an air atmosphere for 20 minutes to obtain P / Mg-C / V2O5, which was recorded as the sample of Example 1.
[0027] Example 2: (1) Weigh 5.0 mmol NH4VO3 and add it to 70 mL of deionized water. Stir and dissolve at 70 °C for 40 min (first stirring). After cooling, a vanadate solution is obtained. Add 85 μL of phytic acid (70%) solution to the above vanadate solution and continue stirring at room temperature for 20 min (second stirring) to obtain a vanadium-phytic acid mixed solution. Add 0.4 mmol MgCl2·6H2O to 15 mL of deionized water and sonicate to dissolve for 20 min. Then, slowly add it dropwise to the above vanadium-phytic acid mixed solution while stirring. Adjust the pH of the mixed system to 3.5 with 0.1 mol / L HCl to finally obtain the precursor solution.
[0028] (2) Take 0.15g of chitosan with a degree of deacetylation ≥90% and add it to 15mL of deionized water, along with 0.17mL of glacial acetic acid. Stir at room temperature for 1.5h to form a homogeneous chitosan solution. Slowly add the above chitosan solution dropwise to the precursor solution, stirring continuously during the addition. After the addition is complete, continue stirring for 1h to form a homogeneous composite hydrogel. Wash the obtained composite gel three times with deionized water. Then place the washed hydrogel in a vacuum freeze dryer and dry at -40℃ for 26h to obtain the composite aerogel precursor.
[0029] (3) The obtained composite aerogel precursor was placed in a tube furnace and heated to 470°C at a heating rate of 5°C / min under a nitrogen atmosphere, and held at that temperature for 2.5 h. After natural cooling, it was heated to 250°C at a heating rate of 5°C / min under an air atmosphere for 25 min to obtain P / Mg-C / V2O5, which was recorded as the sample of Example 2.
[0030] Example 3: (1) Weigh 5.0 mmol NH4VO3 and add it to 100 mL of deionized water. Stir and dissolve at 85 °C for 25 min (first stirring). After cooling, a vanadate solution is obtained. Add 120 μL of phytic acid (70%) solution to the above vanadate solution and continue stirring at room temperature for 30 min (second stirring) to obtain a vanadium-phytic acid mixed solution. Add 0.65 mmol MgCl2·6H2O to 30 mL of deionized water and sonicate to dissolve for 40 min. Then, slowly add it dropwise to the above vanadium-phytic acid mixed solution while stirring. Adjust the pH of the mixed system to 4.5 with 0.1 mol / L HCl to finally obtain the precursor solution.
[0031] (2) Take 0.30 g of chitosan with a degree of deacetylation ≥ 90% and add it to 25 mL of deionized water, along with 0.22 mL of glacial acetic acid. Stir at room temperature for 4 h to form a homogeneous chitosan solution. Slowly add the above chitosan solution dropwise to the precursor solution, stirring continuously during the addition process. After the addition is complete, continue stirring for 4 h to form a homogeneous composite hydrogel. Wash the obtained composite gel three times with deionized water. Then place the washed hydrogel in a vacuum freeze dryer and dry at -50℃ for 22 h to obtain the composite aerogel precursor.
[0032] (3) The obtained composite aerogel precursor was placed in a tube furnace and heated to 520°C at a heating rate of 5°C / min under a nitrogen atmosphere, and held at that temperature for 1.5 h. After natural cooling, it was heated to 300°C at a heating rate of 5°C / min for 15 min in an air atmosphere to obtain P / Mg-C / V2O5, which was recorded as the sample of Example 3.
[0033] Comparative Example 1 (Ordinary V2O5): 5 mmol of NH4VO3 was weighed and placed in a porcelain boat. The temperature was increased to 500℃ at a rate of 5℃ / min under air atmosphere and held for 2 hours. After naturally cooling to room temperature, the resulting solid product was collected, ground evenly, and ordinary V2O5 was obtained, which was recorded as the sample of Comparative Example 1.
[0034] Comparative Example 2 (Preparation of Carbon-Confined V2O5): The difference between Comparative Example 2 and Example 1 is that phytic acid solution and MgCl2·6H2O are not added in step (1). When no corresponding raw materials are added, an equal volume of deionized water is used to make up the difference so that the total volume of the precursors in each group remains consistent. The remaining preparation steps are the same as in Example 1, and the resulting sample is recorded as Comparative Example 2.
[0035] Comparative Example 3 (Preparation of phytic acid-controlled carbon-confined V2O5): The difference between Comparative Example 3 and Example 1 is that MgCl2·6H2O is not added in step (1). When no corresponding raw materials are added, an equal volume of deionized water is used to make up the difference so that the total volume of the precursors in each group remains consistent. The remaining preparation steps are the same as in Example 1, and the resulting sample is recorded as Comparative Example 3.
[0036] Comparative Example 4 (Preparation of Magnesium-Controlled Carbon-Confined V2O5): The difference between Comparative Example 4 and Example 1 is that phytic acid is not added in step (1), and when no corresponding raw materials are added, an equal volume of deionized water is used to make up the difference so that the total volume of the precursors in each group remains consistent. The remaining preparation steps are the same as in Example 1, and the resulting sample is recorded as Comparative Example 4.
[0037] Comparative Example 5 (Preparation of V2O5 regulated by phytic acid-magnesium with weakened carbon confinement structure): The difference between Comparative Example 5 and Example 1 is that the calcination conditions in the second stage of step (3) are changed to calcination temperature of 500℃ and holding time of 2h. The remaining preparation steps are the same as in Example 1. The resulting sample is recorded as Comparative Example 5.
[0038] Example 1 Characterization Analysis: The P / Mg molar ratio of the samples in Examples 1-3 was calculated (the calculation results are shown in Table 1).
[0039] As shown in Table 1, the P / Mg molar ratio is expressed as the ratio of the amount of phosphorus in phytic acid to the amount of magnesium in magnesium salt. The results show that the P / Mg molar ratios in Examples 1-3 are all within the range defined by this invention, indicating that this invention maintains a suitable ratio between the P and Mg components in the preparation system by controlling the amounts of phytic acid and magnesium salt. This ratio is beneficial for the phytic acid-derived P and Mg components to jointly play a regulatory role in precursor formation and subsequent heat treatment, thereby providing conditions for obtaining V-based nanozyme materials with superior structural characteristics and peroxidase-like activity.
[0040] XRD tests were performed on the sample from Example 1 (test results are shown in [link]). Figure 1 SEM EDS-mapping test (test results can be found in...) Figure 2 XPS test (test results can be found in...) Figure 3 (See Table 1) EPR test (test results are shown in Table 1) Figure 4 EIS test (test results are available in [link]). Figure 5 (See Table 1) and nitrogen adsorption-desorption curve test (test results are shown in Table 1).
[0041] V was performed on Examples 2-3 respectively. 4+ Proportion determination (test results are shown in Table 1), EIS test (test results are shown in Table 1), and nitrogen adsorption-desorption test (test results are shown in Table 1).
[0042] Comparative samples 1-5 were subjected to V 4+ Proportioning determination (test results are shown in Table 1), EPR test (test results are shown in Table 2) Figure 4 EIS test (test results are shown in Table 1) and nitrogen adsorption-desorption test (test results are shown in Table 1).
[0043] EIS testing conditions: Electrochemical tests were performed on a Shanghai Chenhua CHI-660E electrochemical workstation (China) using a typical three-electrode system, including a counter electrode (platinum wire), a reference electrode (Hg / HgO electrode), and the prepared working electrode. All electrochemical measurements were performed after 10 cycles of cyclic voltammetry (CV). Electrochemical impedance spectroscopy (EIS) tests were performed in the frequency range of 100 kHz to 0.01 Hz.
[0044] The XRD results of the sample from Example 1 were analyzed, such as... Figure 1 As shown, a set of characteristic diffraction peaks belonging to the V2O5 crystalline phase appeared in the sample. The positions of the main diffraction peaks were basically consistent with those on the V2O5 standard card, indicating that a product with V2O5 as the main crystalline phase was formed after calcination heat treatment. Simultaneously, weak diffraction signals related to the (002) crystal plane of the carbon phase were observed in the spectrum, indicating that the sample retained a certain amount of low-graphitization or amorphous carbon. This carbon component exists as a carbon-confined structure in the V2O5 nanostructure, which can participate in the construction of the carbon / vanadium oxide composite interface to a certain extent and provide a structural basis for subsequent improvement of interface charge transfer performance. In addition, no independent diffraction peaks clearly belonging to crystalline Mg or P-related compounds were observed, indicating that Mg and P-related species did not form impurity phases recognizable by XRD. Figure 2As shown in the SEM EDS-mapping, the sample of Example 1 exhibits a loose structure formed by interlacing and connecting lamellar layers, with certain gaps observed between the layers, and no obvious large-area dense accumulation. EDS elemental mapping results show that V, O, Mg, P, and C elements are all detectable in the observed region, with V and O element signals showing a good spatial correspondence with the regions where the sample lamellar layers are located. Mg and P elements are generally dispersed in this region, with no obvious large-size local enrichment observed. These results indicate that Mg and P-related components have been introduced into the V₂O₅ sample system. Combined with the C elemental mapping signal and the weak carbon-phase-related diffraction signal observed in the XRD pattern, it can be concluded that carbon components are retained in the sample and coexist with the V₂O₅-based structure, providing characterization evidence for the formation of a carbon-confined composite structure. Figure 3 As shown, the V 2p high-resolution XPS spectrum of the sample in Example 1, after peak fitting, shows that at V 2p... 3 / 2 and V 2p 1 / 2 All regions can be clearly identified as belonging to V. 5+ and V 4+ The fitted components indicate that the V element on the sample surface is V 5+ and V 4+ Mixed valence states exist. The area of the fitted peak corresponding to each valence state is calculated, and the surface V of the sample in Example 1 is... 4+ The proportion is approximately 45.1%. As shown in Table 1, this proportion is higher than that of Examples 2 and 3, and the comparative examples, indicating that under the preparation conditions involving both phytic acid-derived P and Mg components, the surface valence state composition of the V₂O₅ samples was regulated, and this was related to the presence of a higher proportion of low-valence V species. Further EPR results show ( Figure 4 Under the same testing conditions, all samples showed oxygen vacancy-related EPR signals around g≈2.003, with the sample from Example 1 exhibiting the highest signal intensity. This result indicates that the sample from Example 1 has a relatively high content of oxygen vacancy-related defects. Figure 5 As shown in Table 1, the charge transfer impedance (Rct) of the sample in Example 1 is 2.43 Ω, the lowest among all tested samples, indicating that the sample in Example 1 exhibits low interfacial charge transfer resistance under this electrochemical testing system. Combined with the analysis of low graphitization or amorphous carbon components in the samples from the aforementioned XRD results, it can be inferred that the retention of an appropriate amount of carbon-confined structure may help improve the interfacial charge transfer capability of the V₂O₅-based nanostructure. Table 1 shows that the nitrogen adsorption-desorption test results indicate that the BET specific surface area of the sample in Example 1 is 142.6 m². 2 / g, pore volume is 0.48cm³ 3The specific surface area and pore volume are relatively high in the tested samples. The large specific surface area and pore volume provide favorable structural conditions for the diffusion of reaction substrates such as H2O2 and TMB, as well as the exposure of potential surface active sites, thereby contributing to improved interfacial utilization efficiency of the catalytic reaction.
[0045] The samples from Examples 2-3 were compared and analyzed with those from Example 1 and the comparative examples, as shown in Table 1. The surface V values of the samples from Examples 2 and 3 were... 4+ The proportions were 44.2% and 43.9%, respectively, which were lower than those of the sample in Example 1, but still significantly higher than those of the other pairs. Their charge transfer impedances (Rct) were 2.47 Ω and 2.52 Ω, respectively, which were slightly higher than those of the sample in Example 1, but still at a low level. Their BET specific surface areas were 135.3 m². 2 / g and 132.0m 2 / g, pore volume is 0.45cm³ 3 / g and 0.43cm 3 / g, all slightly lower than the sample of Example 1, but still maintaining a large specific surface area and pore volume. The above results indicate that although the samples of Example 2 and Example 3 have a higher surface area and pore volume, the Vg of the sample is still lower than that of the sample of Example 1. 4+ While there are some differences from Example 1 in terms of proportions, interfacial charge transfer resistance, and pore structure parameters, the overall sample still maintains a high proportion of low-valence V sites, low interfacial charge transfer resistance, and a relatively open porous structure. This demonstrates that, within the range of component amounts and process conditions defined in this invention, the obtained sample can still maintain superior carbon-confined defect structure characteristics.
[0046] The sample of Comparative Example 1 was compared and analyzed with samples from Examples 1-3 and other comparative examples. Table 1 shows that the surface V of Comparative Example 1... 4+ The proportion was 11.2%, significantly lower than that of samples in Examples 1-3 and other comparative examples, indicating that the proportion of low-valence V sites on the surface in Comparative Example 1 was relatively low. Its charge transfer impedance Rct was 40.55 Ω, the highest among the tested samples, indicating a large interfacial charge transfer resistance and relatively weak electron transport capability. Furthermore, its BET specific surface area was 41.7 m². 2 / g, pore volume 0.15cm³ 3 The concentrations of [amount] / g were also lower than those in Examples 1-3 and other comparative samples, indicating that the openness of their pore structure and the available interface area were relatively limited. For example... Figure 4 As shown, the oxygen vacancy-related EPR signal intensity of the sample in Comparative Example 1 is relatively the lowest, indicating that its oxygen vacancy-related defect content is relatively the lowest.
[0047] The sample of Comparative Example 2 was compared and analyzed with samples from Examples 1-3 and other comparative examples. Table 1 shows that the surface V of Comparative Example 2... 4+The proportion was 14.9%, only slightly higher than that of Comparative Example 1, but significantly lower than that of Examples 1-3, indicating that carbon confinement treatment alone has a limited effect on increasing the proportion of low-valence V sites on the surface. Its charge transfer impedance Rct was 25.60 Ω, lower than that of Comparative Example 1, but still significantly higher than that of Examples 1-3, indicating that its interfacial charge transfer resistance remains high, and the improvement in electron transport capability is limited. Furthermore, the BET specific surface area of Comparative Example 2 was 50.3 m². 2 / g, pore volume is 0.22cm³ 3 / g, which is higher than that of Comparative Example 1, but still significantly lower than that of Examples 1-3. Additionally... Figure 4 As shown, the oxygen vacancy-related EPR signal intensity of the Comparative Example 2 sample is significantly weaker than that of the Example 1 sample, indicating that its oxygen vacancy-related defect content is relatively low. These results indicate that the carbon confinement structure alone can improve the pore structure and interfacial electron transport characteristics of ordinary V₂O₅ to some extent, but its effect on the construction of low-valence V sites and oxygen vacancy-related defects is relatively limited.
[0048] The comparative analysis was performed on sample 3, samples from Examples 1-3, and other comparative examples. Table 1 shows that the surface V of sample 3... 4+ The proportion was 37.1%, lower than that of samples from Examples 1-3, but higher than that of the other comparative examples, indicating that the proportion of low-valence V sites on the surface of the sample was significantly increased under the condition of introducing phytic acid but not Mg. Its charge transfer impedance Rct was 4.79 Ω, higher than that of samples from Examples 1-3, but lower than that of the other comparative examples, indicating that its interfacial charge transfer resistance was increased compared to the example samples. Furthermore, the BET specific surface area of Comparative Example 3 was 95.5 m². 2 / g, pore volume 0.30cm³ 3 / g, all were lower than those of the samples in Examples 1-3, but higher than those of the other comparative examples. For example... Figure 4 As shown, the oxygen vacancy-related EPR signal intensity of Comparative Example 3 was lower than that of Example 1, but stronger than that of the other comparative examples, indicating that its oxygen vacancy-related defect content was relatively high. These results indicate that the phytic acid-derived P component is an important factor promoting the formation of low-valence V sites and oxygen vacancy-related defects. This may be because phytic acid molecules contain multiple phosphate groups, which can coordinate or interact with vanadium species during precursor formation, thereby altering the local coordination environment of VO and promoting or stabilizing the formation of low-valence V sites and oxygen vacancy-related defects. However, although Comparative Example 3 showed a significant defect regulation effect, its defect regulation and interface electron transfer improvement effects were still weaker than those of Examples 1-3, which were regulated by both phytic acid and Mg, without the introduction of the Mg component. This indicates that the structural features of the example samples did not simply originate from increased carbon content or phytic acid regulation alone, but were the result of the combined effects of the phytic acid-derived P component, the Mg component, and the carbon-confined structure.
[0049] The comparative analysis was performed on sample 4, samples from Examples 1-3, and other comparative examples. Table 1 shows that the surface V of sample 4... 4+ The proportion was 15.7%, slightly higher than that of Comparative Examples 1 and 2, but significantly lower than that of Examples 1-3 and Comparative Examples 3 and 5, indicating that the introduction of Mg alone has a limited effect on increasing the proportion of low-valence V sites on the surface. Its charge transfer impedance Rct was 18.14 Ω, lower than that of Comparative Examples 1 and 2, but still higher than that of Examples 1-3 and Comparative Examples 3 and 5, indicating that its interfacial charge transfer resistance is still relatively high, and the improvement in electron transport capability is limited. Furthermore, the BET specific surface area of Comparative Example 4 was 66.1 m². 2 / g, pore volume is 0.26cm³ 3 / g, which is higher than that of Comparative Examples 1 and 2, but still lower than that of Examples 1-3 and Comparative Examples 3 and 5. Additionally... Figure 4 As shown, the oxygen vacancy-related EPR signal intensity of Comparative Example 4 sample is weaker than that of Sample 1, as well as Comparative Examples 3 and 5, indicating that its oxygen vacancy-related defect content is relatively low. These results indicate that Mg, when present alone, can influence the pore structure and interfacial electron transfer characteristics of the samples to some extent, but its effect on the construction of low-valence V sites and oxygen vacancy-related defects is limited, and its regulatory effect is significantly weaker than that of samples involving phytate-derived P components. This may be due to the presence of Mg... 2+ It mainly affects precursor assembly by coordinating or electrostatically interacting with oxygen-containing groups in the system. However, it lacks a polyphosphate group structure similar to phytic acid-derived P components, and its ability to regulate the local chemical environment and surface valence distribution of VO is relatively limited. Therefore, it is difficult to effectively increase the proportion of low-valence V sites and the content of oxygen vacancy-related defects by introducing Mg components alone.
[0050] The comparative analysis was performed on sample 5, samples from Examples 1-3, and other comparative examples. Table 1 shows that the surface V of sample 5... 4+ The proportion was 24.6%, lower than that of samples 1-3 and Comparative Example 3, but higher than that of Comparative Examples 1, 2, and 4. This indicates that even in the presence of the P / Mg component, a certain proportion of low-valence V sites were retained in the sample, but the proportion decreased after treatment at higher temperatures in an air atmosphere. Its charge transfer impedance Rct was 10.43 Ω, higher than that of samples 1-3 and Comparative Example 3, indicating increased interfacial charge transfer resistance and relatively weakened electron transport capability. Furthermore, its BET specific surface area was 78.4 m². 2 / g, pore volume is 0.28cm³ 3 / g, all were lower than those of samples in Examples 1-3 and Comparative Example 3, indicating a decrease in the openness of its pore structure and the available interface area. Additionally, Figure 4 As shown, the oxygen vacancy-related EPR signal intensity of Comparative Example 5 is weaker than that of Sample 1 and Comparative Example 3, indicating that its oxygen vacancy-related defect content is relatively low. These results suggest that although Comparative Example 5 still contains P / Mg components and retains certain low-valence V sites, its carbon composition, surface valence state, and pore structure may have changed after strong air heat treatment, thus affecting its V... 4+ The proportion, oxygen vacancy-related EPR signal, pore structure parameters, and interfacial charge transfer performance were all lower than those of Example 1. These results indicate that the reduction in carbon content and structural reconstruction caused by intense air heat treatment are detrimental to maintaining the original defect, pore structure, and interfacial charge transfer characteristics of the material.
[0051] Table 1 shows the XPS, EIS, and nitrogen adsorption-desorption curves of samples from Examples 1-3 and Comparative Examples 1-5. The test results are expressed as V... 4+ Proportion (%), Rct (Ω), BET specific surface area (m²) 2 / g) and pore volume (cm³) 3 The P / Mg molar ratio in the samples of Examples 1-3 is also listed in Table 1 ( / g).
[0052] Table 1 Example 1 45.1 2.43 142.6 0.48 1.82:1 Example 2 44.2 2.47 135.3 0.45 1.94:1 Example 3 43.9 2.52 132.0 0.43 1.68:1 Comparative Example 1 11.2 40.55 41.7 0.15 / Comparative Example 2 14.9 25.60 50.3 0.22 / Comparative Example 3 37.1 4.79 95.5 0.30 / Comparative Example 4 15.7 18.14 66.1 0.26 / Comparative Example 5 24.6 10.43 78.4 0.28 /
[0053] Experimental Example 2: Peroxidase-like Activity Assay: POD-like activity was tested on samples from Examples 1-3 and Comparative Examples 1-5 (test results are shown in...). Figure 6 The testing method is as follows: Nanozyme solutions (1 mg / mL), TMB (3,3',5,5'-tetramethylbenzidine) (0.8 mM), and H2O2 (70 mM) solutions from Examples 1-3 and Comparative Examples 1-5 were prepared using pure water. Subsequently, 50 µL of suspensions from Examples 1-3 and Comparative Examples 1-5, 200 µL of H2O2, and 200 µL of TMB were mixed in 2550 µL of sodium acetate-acetic acid (NaAc-HAc, pH=4.5) buffer solution. After incubation at 37 °C for 10 min, the absorbance of the reaction solution was measured at 652 nm using a UV-Vis spectrophotometer to evaluate the POD-like activity of each sample.
[0054] like Figure 6 As shown, the order of POD-like activity of each sample in the TMB-H2O2 system is: Sample 1 of Example > Sample 2 of Example > Sample 3 of Example > Sample 3 of Comparative Example > Sample 5 of Comparative Example > Sample 4 of Comparative Example 2 > Sample 1 of Comparative Example. The surface V of the ordinary V2O5 sample in Comparative Example 1...4+ The proportion, oxygen vacancy-related EPR signal, BET specific surface area, and pore volume were all low, and the Rct was high, indicating that its POD-like response was the weakest. The carbon-confined V2O5 sample in Comparative Example 2 showed some improvement compared to Comparative Example 1, but its low-valence V sites and oxygen vacancy-related defect content were still low, indicating that carbon confinement treatment alone had limited effect on improving POD-like activity.
[0055] Comparative Example 3, when only phytic acid-derived P component was introduced, already showed a high V. 4+ The P component exhibited a higher proportion, stronger oxygen vacancy-related EPR signal, and lower Rct, resulting in significantly higher POD-like activity compared to ordinary V₂O₅, carbon-confined V₂O₅, and Mg-controlled samples. This indicates that the introduction of the P component significantly contributes to the enhancement of the colorimetric response. In Comparative Example 4, the introduction of only the Mg component resulted in limited improvement in POD-like activity, suggesting that Mg alone is insufficient to effectively construct a highly active defect interface. However, in the presence of the P component, the Mg component further reduced Rct, increased BET specific surface area and pore volume, and improved the surface V₂O₅ of the samples from Examples 1-3. 4+ The proportions remained at a high level; among them, the sample of Example 1 also exhibited a stronger oxygen vacancy-related EPR signal. These structural and interfacial features resulted in higher POD-like activities for samples of Examples 1-3 compared to Comparative Examples 3 and 4. This indicates that the role of Mg is mainly manifested in the auxiliary synergistic optimization of defect interfaces, open pore structures, and charge transfer processes in the presence of P, rather than acting as the sole primary source of catalytic activity. Comparative Example 5, after strong air treatment, showed a weakened carbon-confined structure, increased Rct, decreased specific surface area and pore volume, and lower POD-like activity than samples of Examples 1-3, indicating that the retention of an appropriate amount of carbon helps maintain a lower interfacial charge transfer impedance and a more open pore structure. In summary, the sample of Example 1 simultaneously possessed a high proportion of low-valence V sites, a strong oxygen vacancy-related defect signal, low charge transfer impedance, and a large specific surface area and pore volume, thus exhibiting the strongest POD-like catalytic response among the tested samples.
[0056] Experimental Example 3: Colorimetric Detection of Uric Acid: Uric acid was detected by colorimetric method on samples from Example 1 and Comparative Examples 1-5 (test results are shown in...). Figure 7(See Table 2) The test method adopted a stepwise cascade reaction approach: 100 μL of PBS (0.015 M, pH=7.5) was mixed with 20 μL of uricase (0.1 mg / mL), 30 μL of uric acid standard solutions with concentrations of 0.5, 1, 2, 5, 10, 20, and 30 mM, and incubated at 37 °C for 40 min. Then, 2800 μL of NaAc-HAc buffer (pH=4.5), 20 μL of the sample suspension (1 mg / mL), and 30 μL of TMB (0.8 mM) were added to the above solution, so that the uric acid concentrations in the final 3.0 mL reaction system were 5 / 10 / 20 / 50 / 100 / 200 / 300 μM, respectively. The mixture was incubated at 37 °C for 10 min. Finally, the absorbance of the reaction solution was measured at 652 nm using a UV-Vis spectrophotometer.
[0057] Figure 7 The UV absorption spectra of the uricase / sample from Example 1 / TMB reaction system at different uric acid (UA) concentrations are shown. Figure 7 a) and the standard curve ( Figure 7 (b) As the UA concentration increased from 5 μM to 300 μM, the content of H2O2 generated by the uricase reaction increased accordingly. The sample of Example 1 further catalyzed the oxidation of TMB by H2O2, causing the system to gradually deepen in blue and the absorbance at 652 nm to gradually increase. The results showed that within the UA concentration range of 5–300 μM, the absorbance at 652 nm had a good linear relationship with the UA concentration, with the linear equation being y = 0.0046x + 0.5426 and the limit of detection (LOD) being 4.5 μM (LOD = 3σ / k, where σ is the noise standard deviation and k is the slope of the standard curve). The results indicated that this system can be used for colorimetric detection of UA. In addition, as shown in Table 2, the LODs of Comparative Examples 1–5 for UA detection were 58.3 μM, 49.1 μM, 8.5 μM, 46.9 μM, and 14.7 μM, respectively, all higher than that of the sample of Example 1. The results are generally consistent with the aforementioned POD-like activity test results, indicating that the catalytic ability of nanozymes in the H2O2 oxidation of TMB is one of the important factors affecting the sensitivity of UA colorimetric detection.
[0058] Table 2 shows the colorimetric detection results of uric acid in the samples of Example 1 and Comparative Examples 1-5. The test results are presented in the form of LOD (μM).
[0059] Table 2 .
[0060] Experimental Example 4: Anti-interference test: An anti-interference test was conducted on the sample from Example 1 (test results are shown in...). Figure 8 The testing method is as follows: The sample suspension (1 mg / mL), uricase solution (0.1 mg / mL), TMB solution (0.8 mM), and solutions of uric acid, dopamine, glucose, ascorbic acid, urea, citric acid, and glycine (150 μM) from Example 1 were prepared using deionized water. Subsequently, 100 μL of PBS buffer (pH=7.5), 50 μL of uricase solution, and 50 μL of each analyte solution were mixed and incubated at 37 °C for 15 min. After incubation, 2700 μL of NaAc-HAc buffer (pH=4.5), 50 μL of the sample suspension from Example 1, and 50 μL of TMB solution were added to the above reaction solution. After further incubation at 37 °C for 15 min, the absorbance of the reaction solution was measured at 652 nm using a UV-Vis spectrophotometer.
[0061] like Figure 8 As shown, under the conditions where common coexisting substances such as dopamine, glucose, ascorbic acid, urea, citric acid, and glycine are present, the absorbance response of the detection system at 652 nm is significantly lower than that caused by uric acid, and the absorbance response caused by each interfering substance does not exceed 15% of the uric acid response value. These results indicate that the aforementioned common coexisting substances have little impact on the uric acid colorimetric detection system constructed in this invention, demonstrating that the system has good anti-interference properties against uric acid.
[0062] Experimental Example 5: Application Evaluation of Artificial Serum Samples: The application of artificial serum samples in Example 1 was evaluated (test results are shown in Table 3). The test methods are as follows: The artificial serum composition is as follows: bovine serum albumin (BSA) 0.1%, NaCl 100mM, NaHCO3 30mM, KCl 5mM, NaH2PO4 1.5mM, CaCl2 1.0mM, glucose 4.5mM, and urea 2.5mM.
[0063] 30 μL of uric acid at different concentrations (5 μM, 10 μM, 30 μM, 60 μM, 100 μM, and 300 μM) was added to artificial serum, replacing the uric acid standard solution in Experiment 3. All other reaction steps and detection conditions remained unchanged. A standard curve was plotted using this method to determine the spiked concentration. Three replicates were performed for each sample, and the spiked recovery rate and intra-batch relative standard deviation (RSD) were calculated.
[0064] Recovery rate % = (Total concentration after spiking - Blank matrix concentration) / Uric acid dosage × 100% As shown in Table 3, the samples from Example 1 were used for the spiked detection and evaluation of uric acid in artificial serum samples. The results showed that within the spiked range of 5–300 μM, the uric acid detection recovery rate was 98.8%–103.1%, and the intra-assay relative standard deviation (RSD) was less than 5%. These results indicate that the uric acid colorimetric detection system constructed in this invention has good detection accuracy and repeatability in an artificial serum matrix, demonstrating its potential application in the detection of uric acid in real biological samples.
[0065] Table 3 shows the uric acid spiking test results in artificial serum samples in Example 1. Table 3 5 4.94 98.8 3.56 10 10.19 101.9 2.13 30 30.00 100.0 1.52 60 59.58 99.3 3.37 100 103.10 103.1 2.34 300 300.90 100.3 2.64 comprehensive Figures 1-8 As shown in Tables 1-3, the sample of Example 1 exhibits a relatively complete V₂O₅ crystal phase, a relatively loose lamellar structure, detectable Mg / P / C elemental signals, a suitable amount of carbon-confined structure, and a high surface V₂. 4+ The sample exhibits a high proportion of oxygen vacancy-related EPR signals, low charge transfer impedance, and a large BET specific surface area and pore volume. These structural and interfacial features provide favorable conditions for the diffusion, contact, and interfacial electron transfer of reactants such as H2O2 and TMB. Therefore, the sample in Example 1 showed superior responses in POD-like activity tests and uric acid cascade colorimetric detection. Combining Example 1 and the comparative example, it can be seen that the phytic acid-derived P component mainly plays a role in defect induction and surface valence state regulation; the Mg component alone has limited improvement, but in the presence of the P component, it can further play an auxiliary synergistic regulatory role, simultaneously improving low-valence V sites, oxygen vacancy-related defects, pore structure parameters, and interfacial charge transfer characteristics; an appropriate amount of carbon confinement structure helps reduce interfacial charge transfer impedance and maintain an open porous structure. It should be noted that the performance improvement of the sample in Example 1 is not simply due to the increase in carbon content, but rather the result of the combined effects of the phytic acid-derived P component, Mg component, and carbon confinement structure. The combined effect of these three factors gives the sample in Example 1 a high V... 4+ The ratio, strong oxygen vacancy-related EPR signal, low Rct, large BET specific surface area and pore volume provide favorable conditions for improving the catalytic interface performance of V2O5 nanozymes.
[0066] As shown in Table 2, the LOD of the sample from Example 1 for uric acid detection was 4.5 μM, which is lower than that of the comparative samples 1-5, indicating that the cascade colorimetric system constructed by the sample from Example 1 has higher sensitivity for uric acid detection. This result is consistent with... Figure 6 The overall trend of POD-like activity changes was consistent, indicating that the ability of nanozymes to catalyze the oxidation of TMB by H2O2 is one of the important factors affecting the colorimetric detection response of uric acid. (See Table 1 and...) Figure 4 It can be seen that the sample in Example 1 also has a high surface V4+ The reaction exhibits a high proportion of oxygen-vacancy correlated EPR signals, low charge transfer impedance, and a large BET specific surface area and pore volume. These characteristics facilitate the diffusion, contact, and interfacial electron transfer of reaction substrates such as H₂O₂ and TMB, thereby enhancing the colorimetric response of TMB oxidation.
Claims
1. A phytic acid-magnesium synergistically regulated carbon-confined defective V2O5 nanozyme for colorimetric detection of uric acid, characterized in that, The nanozyme comprises a V₂O₅ crystalline phase, a carbon-confined structure, and phytic acid-derived P and Mg components; the nanozyme has the following physicochemical characteristics: (a) Surface V 4⁺ The proportion is no less than 43.9%; (b) The intensity of oxygen vacancy-related electron paramagnetic resonance (EPR) signal was higher than that of control samples regulated by phytate alone or magnesium alone; (c) The charge transfer impedance Rct is not higher than 3.0Ω; (d) The specific surface area of BET is not less than 130 m² / g, and the pore volume is not less than 0.40 cm³ / g.
2. The phytic acid-magnesium synergistically regulated carbon-confined defective V2O5 nanozyme for colorimetric detection of uric acid according to claim 1, characterized in that, The carbon confined structure exhibits a weak diffraction signal of the carbon (002) crystal plane in the X-ray diffraction pattern within the range of 2θ≈24°~26°.
3. A method for preparing a phytic acid-magnesium synergistically regulated carbon-confined defective V2O5 nanozyme for colorimetric detection of uric acid, comprising the following steps: (1) Dissolve ammonium metavanadate in deionized water, stir at 70~85℃ to dissolve, cool and add phytic acid solution, stir at room temperature to obtain vanadium-phytic acid mixed solution; Magnesium chloride hexahydrate was added to deionized water, dissolved by sonication, and then added dropwise to the vanadium-phytic acid mixed solution under stirring. The pH was adjusted to 3.5-4.5 with hydrochloric acid to obtain the precursor solution. (2) Dissolve chitosan in deionized water containing glacial acetic acid and stir at room temperature to form a chitosan solution. Add the chitosan solution dropwise to the precursor solution in step (1). Continue stirring after the addition is complete to form a composite hydrogel. After washing and freeze-drying, a composite aerogel precursor is obtained. (3) The composite aerogel precursor is placed in a tube furnace and calcined at 470~520℃ under a nitrogen atmosphere for 1.5~2.5h. After natural cooling, it is calcined at 250~300℃ under an air atmosphere for 15~25min to obtain the phytic acid-magnesium synergistic carbon confinement defective V2O5 nanozyme for uric acid colorimetric detection.
4. The preparation method according to claim 3, characterized in that, In step (1), the ratio of ammonium metavanadate to phytic acid is 5.0 mmol of ammonium metavanadate to 85~120 μL of phytic acid solution, and the mass percentage concentration of the phytic acid solution is 70%; the amount of magnesium chloride hexahydrate is 0.4~0.65 mmol.
5. The preparation method according to claim 3, characterized in that, In step (1), the molar ratio of P in phytic acid to Mg in magnesium chloride hexahydrate is 1.68:1 to 1.94:
1.
6. The preparation method according to claim 3, characterized in that, In step (2), the amount of chitosan used is 0.15~0.30g, and the degree of deacetylation of the chitosan is ≥90%; the amount of glacial acetic acid used is 0.17~0.22mL, and the amount of deionized water used is 15~25mL; the freeze-drying temperature is -50 to -40℃, and the time is 22~26h.
7. The preparation method according to claim 3, characterized in that, In step (3), the heating rate of the first calcination stage is 5℃ / min, the holding temperature is 490~510℃, and the holding time is 1.8~2.2h; the heating rate of the second calcination stage is 5℃ / min, the holding temperature is 270~290℃, and the holding time is 18~22min.
8. The preparation method according to claim 3, characterized in that, The ultrasonic dissolution time in step (1) is 20~40 min, and the pH is adjusted to 4.0; the stirring time after the drop addition in step (2) is 1~4 h.
9. The application of the phytic acid-magnesium synergistic carbon confinement defective V2O5 nanozyme for uric acid colorimetric detection prepared by any one of claims 3-8 in the preparation of uric acid detection reagents or detection systems.
10. The application according to claim 9, characterized in that, The uric acid detection is a colorimetric detection method. The detection principle is as follows: uric acid generates hydrogen peroxide under the action of uric acid oxidase. The hydrogen peroxide is catalyzed by the phytic acid-magnesium synergistic carbon confined defect type V2O5 nanozyme used for uric acid colorimetric detection, which oxidizes 3,3',5,5'-tetramethylbenzidine (TMB) to produce a blue oxidation product. The quantitative detection of uric acid is achieved by measuring the change in absorbance at a wavelength of 652 nm. The linear range of the detection is 5~300μM, the limit of detection is not higher than 4.5μM, and the recovery rate in artificial serum samples is 98.8%~103.1%, with an intra-batch relative standard deviation (RSD) of less than 5%.
